Corak dan Warna-warni Islam Nusantara: Awal, Tengah dan Modern - Nicodemus Boenga (Universitas Islam Negeri Fatmawati Sukarno, 2020)
AbstractSubstantially, Islam is not restricted as a belief that appeared in the first century Hijri in the Arabian Peninsula. Islam itself has existed long before Islam formally became a religion. It exists and is manifested in many forms. It is intertwined with a variety of customs, cultures, and traditions before Qur’an was orally revealed by God to the final prophet, Muhammad. In fact, at that time, the substantive values of Islam had not strongly yet influenced the Arab region or the world. It was considered to already existed. That is why Adam, Abraham, Moses and another figure born before Muhamad were considered to be Prophets of Islam. Similarly with the presence of “Islam of the Archipelago (Islam Nusantara)” in Indonesia. This kind of Islam is neither something out there that comes nor something that just exists in Indonesia but it is the real nature of Islam. Thus, Islam of the Archipelago became a model of thought, understanding, and experience that promotes how local culture, wherever it may be, can interact positively with Islamic beliefs and practices substantially which is reflected in Rahmatan Lil Alamin’s Islam.Abstrak Sejatinya substansi Islam bukanlah temuan yang baru muncul pada abad pertama Hijriah di mana agama Islam lahir di Jezirah Arab. Substansi Islam sudah ada sebelum Islam secara formal menjadi sebuah agama. Substansi itu ada dan terjelma dalam berbagai konteks, lokus dan masa. Islam berkelindan dengan ragam adat, budaya dan tradisi keyakinan sebelum turunnya Al-Quran kepada Nabi Muhamad, walaupun kenyataannya nilai-nilai substantif Islam belum dominan menggarami konteks Arab atau dunia pada waktu itu. Itulah sebabnya Adam, Abraham, Musa dan nama-nama lainnya yang lahir sebelum Muhamad dianggap sebagai Nabi Islam. Demikian halnya dengan Islam Nusantara. Kehadirannya bukanlah dari luar dan kebetulan ada di Indonesia tetapi itulah wajah Islam di Indonesia. Islam Nusantara membawa corak dan warna-warni tersendiri sesuai konteksnya. Islam Nusantara menjadi model pemikiran, pemahaman, dan pengalaman ajaran-ajaran Islam yang dikemas secara kontekstual melalui budaya dan tradisi lokal yang berkembang di Nusantara sehingga tetap mencerminkan Islam yang Rahmatan Lil Alamin.